Hubungan Pelaksanaan Usaha Kesehatan Gigi Sekolah terhadap Status Karies Gigi : Literature Review - Hayyu Failasufa; Thania Olivia Fahrie; Arimbi Arimbi (Indonesian Journal of Dentistry, 2021)
Background: Dental caries is a oral disease with a high prevalence in paediatric dentistry that can affect the quality of life. Around 60%-90% of school-age children in the world are affected by caries and in Indonesia the prevalence of caries in children aged 5-9 years reaches 92.6%. Caries is caused by many factors, one of which is the low level of oral health education. UKGS (School Dental Health Program) is one of the effective and efficient promotive and preventive efforts. A literature review was conducted the relationship between the implementation of School Dental Health Program with dental caries status in school-age children. Method: Literature review research with a systematic approach, using data sources from the Google Scholar, PubMed and Science Direct databases. Result: A literature review conducted from 21 articles showed that the School Dental Health Program was related to the dental caries status of school-age children. Schools that implement the School Dental Health Program well have children with low dental caries status. Conclusion: There is a relationship between the School Dental Health Program and dental caries status in school-age children.